2021
DOI: 10.4012/dmj.2020-232
|View full text |Cite
|
Sign up to set email alerts
|

Can polylactic acid be a CAD/CAM material for provisional crown restorations in terms of fit and fracture strength?

Abstract: This study aimed to evaluate polylactic acid (PLA) as a provisional crown material. Lower right first molar phantom tooth was used for the fabrication of 60 crowns. Samples were divided into three groups (n=20) according to the material: Group PL (PLA), Group PM (polymethyl methacrylate), and Group PE (polyetheretherketone). Each group was investigated for internal and marginal fit, fracture strength, and fracture mode. Data were analyzed using ANOVA, chi-squared test, and Tukey's tests (p≤0.05). The average m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Moreover, in the study carried out by Merve [46], where they studied two different groups of materials for use in interim restorations (milled PMMA and polylactic acid for printed restorations), the fracture resistance values obtained from the group of the milled PMMA interim restorations were located at 752.00 N, while the value for the impression interim restorations was 681.00 N. These values give results of a greater resistance to fracture for the interim restorations obtained using the milled technique, similar to the results obtained by the present study. The values presented by Merve, however, are lower; this may be due to several factors, including that the work carried out by the author, Merve, was on individual crowns, while the present study was carried out on a three-unit bridge [46]. A comparative table of results of several studies and our results is showed in table.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the study carried out by Merve [46], where they studied two different groups of materials for use in interim restorations (milled PMMA and polylactic acid for printed restorations), the fracture resistance values obtained from the group of the milled PMMA interim restorations were located at 752.00 N, while the value for the impression interim restorations was 681.00 N. These values give results of a greater resistance to fracture for the interim restorations obtained using the milled technique, similar to the results obtained by the present study. The values presented by Merve, however, are lower; this may be due to several factors, including that the work carried out by the author, Merve, was on individual crowns, while the present study was carried out on a three-unit bridge [46]. A comparative table of results of several studies and our results is showed in table.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the fracture resistance of temporary restorations using innovative CAD/CAM techniques in the workflow has the potential to generate greater productivity for the clinician. The low values obtained from the provisional restorations made by 3D printing show that they can be used, as the author Merve cites, in cases in which they will not be subjected to high chewing loads, providing a second quality clinical option [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant difference in fracture mode was discovered between provisional and permanent crowns (p=0.001). However, few studies on provisional crown fracture modes -particularly PEEK and PPSU fracture modes -are similar to recent provisional CAD/CAM crowns (12,24) . In this analysis, PEEK crowns had the most prevalence of Class II fractures (loss of less than half the crown), whereas PPSU crowns were most commonly reported with Class III fractures (loss or displacement of half the crown).…”
Section: Discussionmentioning
confidence: 99%
“…A provisional restoration's success is directly affected by its fit, as poor adaptation will cause the final restoration to be delivered late. This is especially true for provisional restorations used in the esthetic zone or planned to last a long time (24) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation